Tanam Selasih (Therapeutic Nape Massage dan Senam Lansia Sehat) sebagai Upaya Pencegahan Komplikasi Hipertensi - Mustain, Mukhamad; Sugiarto, Heri; Minardo, Joyo; Maksum (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2025)
Hypertension is a non-communicable disease that is commonly experienced by the elderly, with a prevalence that continues to increase. Uncontrolled hypertension, where systolic blood pressure is ≥140 mmHg and diastolic blood pressure is ≥90 mmHg, can lead to various complications such as heart disease, stroke, kidney failure, and vision disturbances. In addition to regular medication, hypertension complications can be minimized with complementary therapies such as Therapeutic Nape Massage and elderly exercises. The results of a preliminary study in the Ngadipiro Walitelon Utara area, Temanggung Regency, found that out of 70 elderly individuals, 54% were experiencing hypertension. Most elderly people do not regularly exercise, such as doing gymnastics, and do not understand alternative treatments for hypertension complications. The purpose of providing Tanam Selasih is to increase the knowledge of the community, especially the elderly, in minimizing hypertension complications and promoting healthy living behaviors through exercise. The activities were conducted using lecture, discussion, and demonstration methods. The activities included blood pressure checks, pre-post tests, education, as well as demonstrations of Therapeutic Nape Massage and elderly exercises. Community service was conducted on Tuesday, December 7, 2024, in the Ngadipiro area, Walitelon Utara. The activity was attended by 36 participants. The results of the community service showed an increase in public knowledge about Tanam Selasih to minimize hypertension complications, where there was a difference in the average knowledge before and after the education with a paired t-test value of 0.000. There is a need for the dissemination of information to a wider community regarding the benefits of planting basil in reducing hypertension complications. There is a need for the dissemination of information to the wider community regarding the benefits of Tanam Selasih in reducing hypertension complications.   ABSTRAK Hipertensi adalah penyakit tidak menular yang banyak dialami oleh lansia dengan prevalensi yang terus meningkat. Hipertensi yang tidak terkendali, dimana ukuran tekanan darah sistolik ³140 mmHg dan tekanan darah diastolik ³90 mmHg dapat memunculkan berbagai komplikasi seperti penyakit jantung, stroke, gagal ginjal dan gangguan penglihatan. Selain dengan pengobatan teratur, komplikasi hipertensi dapat diminimalisir dengan tindakan  terapi komplementer seperti Therapeutic Nape Massage (pijat tengkuk) dan senam lansia sehat (Tanam Selasih).   Hasil   studi   pendahuluan   di lingkungan   Ngadipiro Walitelon   Utara   Kab Temanggung, dari 70 lansia ditemukan 54% yang mengalami hipertensi. Sebagian besar lansia juga belum rutin berolahraga seperti senam dan belum memahami pencegahan alternatif komplikasi hipertensi. Tujuan kegiatan pengabdian kepada masyarakat Tanam Selasih yaitu  untuk  meningkatkan  pengetahuan  masyarakat khususnya lansia  dalam  meminimalkan komplikasi hipertensi dan meningkatkan perilaku hidup sehat melalui senam. Kegiatan  dilakukan  dengan  metode  ceramah,  diskusi dan demonstrasi.  Kegiatan meliputi  pemeriksaan  tekanan  darah,  pre-posttest,  edukasi  serta demonstrasi Therapeutic Nape Massage dan senam lansia. Pengabdian kepada masyarakat dilaksanakan pada hari sabtu tanggal 7 Desember 2024  bertempat  di  lingkungan Ngadipiro,  Walitelon  Utara Kab Temanggung.  Kegiatan  diikuti  oleh  30  peserta.  Hasil pengabdian  kepada  masyarakat  didapatkan  peningkatan  pengetahuan  masyarakat  mengenai tanam selasih  dalam  meminimalkan komplikasi hipertensi  dimana  ada  perbedaan  rata-rata pengetahuan  sebelum  dan  sesudah  edukasi  dengan  nilai  uji  t  berpasangan  0.000. Perlu  adanya penyebarluasan informasi kepada masyarakat yang lebih luas mengenai manfaat tanam selasih dalam menurunkan komplikasi hipertensi.